Integrating Interactive and Mobile Learning Technologies in Pre-Service EFL Teacher Education - Dmitrenko, Natalia; Panchenko, Violetta (International Journal of Interactive Mobile Technologies (iJIM), 2025)
A virtual educational environment has come into being in English as a Foreign Language (EFL) classrooms since the COVID-19 pandemic. The study introduces various online tools and activities designed to foster engagement and motivation among pre-service EFL teachers. The authors share hands-on experience from exploring interactive platforms and web resources, including Online Test Pad, YouGlish, FluentU, Readers Theater, Voki, Kialo, Edpuzzle, Padlet, and digital dictionaries; highlight their pros and cons; discuss the effectiveness of each tool for a particular teaching purpose; and introduce practice-based strategies for effective integration of online tools into pre-service EFL teacher instruction. The authors explore how online games combine practice with competition and interaction to increase engagement; discover the potential of pattern poems, readers theater, and discussion forums in constructing narratives using target vocabulary and grammar while also honing speaking and writing skills; and suggest tips on using animated platforms for personalizing writing prompts and providing feedback on written work. The analysis of survey results of pre-service teachers’ feedback is presented to justify that incorporating interactive online activities can tap into intrinsic motivation and create a more enjoyable and effective learning experience.